2013
DOI: 10.1002/ajh.23403
|View full text |Cite
|
Sign up to set email alerts
|

Neurofibromatosis‐1 gene deletions and mutations in de novo adult acute myeloid leukemia

Abstract: On behalf of the French ALFA groupGermline heterozygous alterations of the tumor-suppressor gene neurofibromatosis-1 (NF1) lead to neurofibromatosis type 1, a genetic disorder characterized by a higher risk to develop juvenile myelomonocytic leukemia and/or acute myeloid leukemia (AML). More recently, somatic 17q11 deletions encompassing NF1 have been described in many adult myeloid malignancies. In this context, we aimed to define NF1 involvement in AML. We screened a total of 488 previously untreated de novo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 25 publications
1
37
0
1
Order By: Relevance
“…75 The only gene in the minimal deleted region was the tumor suppressor gene NF1 (tumorsuppressor gene neurofibromatosis-1). 75 The relatively high incidence of NF1 deletions in inv (16) AML found in that study still needs to be confirmed, because in other studies, the incidence of NF1 deletions in CBF-AML did not exceed 2% 79,80 and was only 4% in the subset of inv(16) AML. 79 In t(8;21) AML with additional del(9q), the putative tumor suppressor genes TLE1 and TLE4 are regularly deleted.…”
Section: Beyond Gene Mutationsmentioning
confidence: 69%
“…75 The only gene in the minimal deleted region was the tumor suppressor gene NF1 (tumorsuppressor gene neurofibromatosis-1). 75 The relatively high incidence of NF1 deletions in inv (16) AML found in that study still needs to be confirmed, because in other studies, the incidence of NF1 deletions in CBF-AML did not exceed 2% 79,80 and was only 4% in the subset of inv(16) AML. 79 In t(8;21) AML with additional del(9q), the putative tumor suppressor genes TLE1 and TLE4 are regularly deleted.…”
Section: Beyond Gene Mutationsmentioning
confidence: 69%
“…Several studies have described del(17q) encompassing NF1 tumor suppressor in myeloid malignancies. 45 We identified NF1 deletion in 5 cases and mutations in 2 PMF cases with no CNAs. These cases evolved in AML or the patients died, suggesting that NF1 alterations may contribute to MF progression and poor outcome.…”
Section: Disease Progression and Prognosis In Myelofibrosismentioning
confidence: 99%
“…Importantly, sequencing of tumour exomes and genomes has revealed that somatic NF1 mutations are present at incidences from 2.5% to 11.8% in sporadic, predominantly adult, tumour types such as lung cancer 32 , glioblastoma 33 , ovarian cancer 34 , breast cancer 35 and acute myeloid leukaemia (AML) 36 ; however, they are also present in the paediatric tumour rhabdomyosarcoma.…”
mentioning
confidence: 99%